2023
DOI: 10.1140/epjqt/s40507-023-00187-w
|View full text |Cite
|
Sign up to set email alerts
|

A study of polarization compensation for quantum networks

Matej Peranić,
Marcus Clark,
Rui Wang
et al.

Abstract: The information-theoretic unconditional security offered by quantum key distribution has spurred the development of larger quantum communication networks. However, as these networks grow so does the strong need to reduce complexity and overheads. Polarization-based entanglement distribution networks are a promising approach due to their scalability and no need for trusted nodes. Nevertheless, they are only viable if the birefringence of all-optical distribution fibres in the network is compensated to preserve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that polarization can be used for atmospheric FSO [16]. The use of optical polarization in communication opens up the realm of quantum communication and quantum internet [17]. However, turbulence in the atmosphere can potentially produce impurities in quantum states.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that polarization can be used for atmospheric FSO [16]. The use of optical polarization in communication opens up the realm of quantum communication and quantum internet [17]. However, turbulence in the atmosphere can potentially produce impurities in quantum states.…”
Section: Introductionmentioning
confidence: 99%